A New Anti-inflammatory Therapy for Chronic Obstructive Pulmonary Disease (COPD) - Qian Zeng (Challenges in Disease and Health Research Vol. 7, 2021)
COPD (Chronic Obstructive Pulmonary Disease) is a chronic progressive inflammatory lung disease, characterized by small airway obstruction and lung alveoli tissue damage. The mainstays of current treatment of COPD are inhaled bronchodilators and ICS (inhaled Corticosteroids). The key issue in the treatment of COPD is to treat the inflammation. But the inflammation in COPD is partially resistant to Steroid. ICS can only temporarily suppress the inflammation in COPD, but not terminates the inflammation, and therefore there is a need to develop new anti-inflammatory therapies or drugs. Artemisia Argyi, also called moxa, is a plant. Its leaves have been used to treat various diseases by traditional Chinese herbalists. The dried moxa fluff is made into a stick to heat certain points on patient’s skin to treat various diseases. This therapy is called moxibustion. Through experiments, the author finds that the mechanism of the moxibustion is that the smoke or tar of the burning moxa has unique anti-inflammatory property, which can treat and cure Steroid resistant chronic non-specific inflammation. The author develops a new anti-inflammatory therapy by the inhalation of moxa smoke to treat 25 COPD patients. 22 of 25 patients became symptoms free after 1 to 2 months treatment and kept symptoms free after the cessation of treatment without any other treatments.